Quantifying the Impact of Industry 4.0 Technologies on Leather Processing Efficiency: A Meta-Analysis - Ajie, Baskoro (HM Publisher, 2024)
Industry 4.0, marked by the integration of digital technologies and automation, presents a transformative opportunity for the leather industry to enhance efficiency and productivity. This meta-analysis aims to quantitatively synthesize the existing evidence on the impact of Industry 4.0 technologies on leather processing efficiency. A systematic search was conducted across multiple databases, including Scopus, Web of Science, and Google Scholar, to identify relevant studies published between 2018 and 2024. Studies reporting quantitative data on the impact of Industry 4.0 technologies on leather processing efficiency were included. Effect sizes were extracted and pooled using random-effects models. The meta-analysis included 25 studies, encompassing a total of 1,250 leather processing facilities. The overall pooled effect size indicated a significant positive impact of Industry 4.0 technologies on leather processing efficiency (Hedges' g = 0.65, 95% CI: 0.48 to 0.82, p < 0.001). Subgroup analyses revealed that the impact varied across different technologies and stages of leather processing. Industry 4.0 technologies have a substantial positive impact on leather processing efficiency. The findings underscore the importance of embracing these technologies for leather manufacturers to remain competitive and meet the growing demand for sustainable and efficient production practices. Future research should explore the long-term impact of these technologies and their potential for further optimization.